The Comparison of Work Motivation Between Generation Z and Millennials Generation - Asmadhini Handayani Rahmah; Rukmana, Gilang Mukti; Rahmadani, Muhammad Harits Zidni Khatib; Lubis, Marsha Anindita (Journal of Social Transformation and Regional Development, 2024)
In line with the ever-changing era, understanding the work motivation of Generation Z and Millennials has become a highly significant issue in the context of human resource management and organizational productivity. Comparing work motivation between Generation Z and Millennials carries significant implications in the context of the workplace, human resource management, and corporate strategy development. Understanding the work motivation of these two generations can help organizations enhance employee engagement and performance. The comparison of work motivation is examined based on influencing variables, including the work environment, work commitment, and individual characteristics. This research employs a quantitative approach with subjects consisting of Generation Z and Millennials in the city of Samarinda. A questionnaire was distributed to collect data regarding their perceptions. The results revealed that work motivation in Generation Z is influenced solely by individual characteristics, while in Millennials, it is affected by the work environment and commitment.